(untitled) (Cahiers Africains de rhétorique, 2025)
Amilcar Cabral was a multidimensional character. His general culture made him considered an agronomist, an urban planner, a poet, a politician, a revolutionary, a sage, a visionary. Having learned from mobility, he had the chance to associate with great leaders and read great works. This had never prevented him from keeping an eye on his own independence of judgment and conduct. He didn’t let himself be hypnotized by anyone. This character trait informs about his state of mind of revolt who also had an eye on the catastrophic situation of his black compatriots who were dying slowly under the abominable colonial and Portuguese dictatorship. He will use all the rhetorical finesse to demand their release and win their independence. Without empty rhetoric, he aroused a lot of admiration and curiosity in this tough and successful journey.